Identification of a tumor-reactive T-cell repertoire in the immune infiltrate of patients with resectable pancreatic ductal adenocarcinoma. (1st December 2016) - Poschke, Isabel; Faryna, Marta; Bergmann, Frank; Flossdorf, Michael; Lauenstein, Claudia; Hermes, Jennifer; Hinz, Ulf; Hank, Thomas; Ehrenberg, Roland; Volkmar, Michael; Loewer, Martin; Glimm, Hanno; et al.
ABSTRACT: Purpose: The devastating prognosis of patients with resectable pancreatic ductal adenocarcinoma (PDA) presents an urgent need for the development of therapeutic strategies targeting disseminated tumor cells. Until now, T-cell therapy has been scarcely pursued in PDA, due to the prevailing view that it represents a poorly immunogenic tumor. Experimental design: We systematically analyzed T-cell infiltrates in tumor biopsies from 127 patients with resectable PDA by means of immunohistochemistry, flow cytometry, T-cell receptor (TCR) deep-sequencing and functional analysis of in vitro expanded T-cell cultures. Parallel studies were performed on tumor-infiltrating lymphocytes (TIL) from 44 patients with metastatic melanoma. Results: Prominent T-cell infiltrates, as well as tertiary lymphoid structures harboring proliferating T-cells, were detected in the vast majority of biopsies from PDA patients. The notion that the tumor is a site of local T-cell expansion was strengthened by TCR deep-sequencing, revealing that the T-cell repertoire in the tumor is dominated by highly frequent CDR3 sequences that can be up to 10, 000-fold enriched in tumor as compared to peripheral blood. In fact, TCR repertoire composition in PDA resembled that in melanoma. Moreover, in vitro expansion of TILs was equally efficient for PDA and melanoma, resulting in T-cell cultures displaying HLA class I-restricted reactivity against autologous tumor cells. Conclusions: The tumor-infiltrating T-cell response in PDA shows striking similarity to that in melanoma, where adoptive T-cell therapy has significant therapeutic impact. Our findings indicate that T-cell-based therapies may be used to counter disease recurrence in patients with resectable PDA.